2019
DOI: 10.17146/aij.2019.862
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Patient Doses in Interventional Cardiology in Indonesia: A Preliminary Result

Abstract: Interventional cardiology is a branch of cardiology that manages the catheter based treatment of structural heart illnesses. These minimally invasive procedures involve inserting catheters and other devices through superficial arterial and venous access sites. Due to increased reliability and advancing technology, the number and complexity of interventional cardiology procedures haves increased in recent years. The increasing complexity of the procedures, however, require longer fluoroscopic duration, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…As can be seen, the CA procedure gave the highest air kerma to the patients, while the highest KAP was received by patients who underwent PCI procedure. These results include those that have been previously reported [21].…”
Section: Resultssupporting
confidence: 87%
“…As can be seen, the CA procedure gave the highest air kerma to the patients, while the highest KAP was received by patients who underwent PCI procedure. These results include those that have been previously reported [21].…”
Section: Resultssupporting
confidence: 87%
“…Therefore, to control the infectious diseases, such as malaria vaccine (21,22) were developed with 150 Gy of gamma rays effective to attenuate malaria parasite. Furthermore, studies on the diagnoses of metabolic diseases with nuclear medicine technique (23) and Microdosimetry in Radiodiagnostic assessment have also been conducted (24). Diagnose of metabolic disease such as diabetes type 2 in the hearth with tc-99m-sestamibi (Myocardial Perfusion Imaging (MPI) and Multiple Gated Acquisition (MUGA) Methods) have been carried out and revealed as a method that plays a pivotal role in the evaluation of coronary artery disease.…”
Section: Safety Assessments and Dosimetermentioning
confidence: 99%
“…Hiswara et al (24) carried out a research to determine the microdosimetry in radiodiagnostic assessment, and stated that interventional cardiology procedures represent the third largest contribution to the collective dose incurred by a population after computed tomography and nuclear medicine. The results showed that the PCI procedure was the most performed during this study, with the highest radiation doses given to the staff.…”
Section: Safety Assessments and Dosimetermentioning
confidence: 99%